ACADEMIC TEACHERS’ RESEARCH COMPETENCY MODEL IN A MODERN MULTICULTURAL EDUCATIONAL ENVIRONMENT (Revista Inclusiones, 2020)
By the end of the 20th century, Russian higher education oriented professors towards the methods and technologies transition, keeping the research activity out of focus. The professional and pedagogical endeavor is based on teaching and educational work. To a lesser extent (in terms of requirements), attention is paid to scientific and research activities. This research paper describes the problem of the relevance of a holistic and consistent process of the professors’ research competency development in a modern multicultural educational environment. The modernization of higher education in Russia implies a high professional level of teaching, and, consequently, a high level of the research competency development, especially in the area of research. The aim is to review options for the professors’ competency models, compiled by scientists and reflected in the presented research papers. At the same time, the authors of the presented research paper offer their model of a competencies system that accompany analysis.